Answer:
Step-by-step explanation:
That means that the given expressions are equal.
100 - 2.5x = 100 + 2.5(5 - x)
100 - 2.5x = 100 + 12.5 - 2.5x
There is no solution to this.
Answer:
( x y -6)² = x² y² - 12 xy + 36
Step-by-step explanation:
<u><em>Explanation:-</em></u>
Given that the expression ( x y -6)²
Apply formula (a-b)² = a² -2ab + b²
( x y -6)² = (xy)² - 2 × xy× 6 + (6)²
= x² y² - 12 xy + 36
( x y -6)² = x² y² - 12 xy + 36
X+3y=18
x+3y-18=18-18
x+3y-18=0
x+3y-18=0 ( << that’s your answer) hope it helps
x^2 - 3x + 9 - 5x + 10 = 0
x^2 - 8x + 19 = 0
Answer:
54 kg
Step-by-step explanation:
Total weight of 7 boys is 392 kg. And other 6 boys total weight is 338 kg.
So the 7th boy's weight is (392-338)=54 kg